2008
DOI: 10.1002/anie.200801332
|View full text |Cite
|
Sign up to set email alerts
|

“Conformational” Solvatochromism: Spatial Discrimination of Nonpolar Solvents by Using a Supramolecular Box of a π‐Conjugated Zinc Bisporphyrin Rotamer

Abstract: "Solvatochromism" is the ability of chromophoric molecules to change their absorption and/or luminescence colors as a result of a change in solvent polarity. [1][2][3][4][5] In principle, solvatochromic shifts are caused by a change in the energy gap between a ground state and excited state of different polarities, since a change in the solvent polarity leads to differential stabilization of these electronic states. Therefore, specific interactions between chromophore and solvent molecules result in variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Therefore, limited studies of environment-dependent complexes have been reported up to the present. [42][43][44][45][46] Conventional MS using electron ionization, chemical ionization, fast atom bombardment, and electro-spray ionization cannot detect large coordination complexes because the weak coordination bonds dissociate during ionization. Cold-spray ionization MS (CSI-MS) is one of the most promising solutions to this problem, 47 as it can detect coordination complexes without dissociation to give the numbers of ligands and metals as well as ions based on the solvent adducts.…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, limited studies of environment-dependent complexes have been reported up to the present. [42][43][44][45][46] Conventional MS using electron ionization, chemical ionization, fast atom bombardment, and electro-spray ionization cannot detect large coordination complexes because the weak coordination bonds dissociate during ionization. Cold-spray ionization MS (CSI-MS) is one of the most promising solutions to this problem, 47 as it can detect coordination complexes without dissociation to give the numbers of ligands and metals as well as ions based on the solvent adducts.…”
Section: -21mentioning
confidence: 99%
“…It should be emphasized that CSI-MS involves solvent adducts very often. 43 The assignment of observed ion peaks is summarized in Table 1. The difference in mass number between the adjacent peaks corresponds to the doubly charged adamantane-based ligand, as shown in Fig.…”
mentioning
confidence: 99%
“…15 Coordination of the pyridyl substituents to the zinc metal centers drives the self-assembly of the complexes, as shown in Figure 1. The ring–dimer complex c -P12·(P2py2) 6 (Figure 1a) consists of a porphyrin nanoring and six P2py2 dimers; these free-base porphyrin dimers have one meso -4-pyridyl substituent on each porphyrin unit to coordinate to the zinc centers of the nanoring.…”
mentioning
confidence: 99%
“…216,217 Their approach was to use 10-(4-pyridyl)-20-(3,5-dialkoxyphenyl)porphyrin dimer 66 as precursor; like the N 2 -linked corner porphyrin dimers 86a and 86b, 104 syn-planar and anti-planar conformers exist. Insertion of Zn(II) induces the formation of the "orthogonal" and "planar" forms of the boxes, by self-complementary coordination of the lateral 4-pyridyl N to the central Zn atom of another molecule.…”
Section: A Host-guest Interactions and Supramolecular Chemistrymentioning
confidence: 99%